RANCANG BANGUN DAN PEMBUATAN MEJA PUTAR MEKANIS··ELEKTRIS UNTUK MENINGKA TKAN KUANTITAS DAN KUALITAS PRODUKSI PENGRAJIN KERAMIK - Puspito, Jarwo; Widarto, Widarto (Universitas Negeri Yogyakarta, 2004)
The goal of this activity is design and manufacturing Rotating Table Machine for Ceramics Handy Craft. The construction simple relatively, portable, simple technology, and simple operation.The Methodology that used is design and manufacturing method that cover geometric modeling, analysis, synthesis and evaluation, working drawing and manufacturing continually.The result of this program is manufacturing Rotating Table Machine for Ceramics Handy Craft. The specification of machine is 110 em length x 70 ern wide x 90 em high. The prime mover is electrical DC motor 20 Volt, 10 Amphere. The working capacity of this machine is the work piece that 300 mm diameter and 550 rnm high. The functional test result that the machine element is good function and the service test result that the machine is easy service. Profit Different no-vucer and vucer is significant and base economics analysis the Break Even Point (BEP) of machine is 15 month.Key word: rotating table machine, and ceramics.